Unfolding the story of dermocosmetics - Ab. Hadi, Hazrina (2018)
Most of the people associate cosmetic product with make-up, which is color cosmetics. However, in the eyes of Food And Drug Administration (FDA), a cosmetic is a product intended to be applied to the human body for cleansing, beautifying, promoting attractiveness, or altering the appearance. This includes beauty preparations (make up, perfume, skin cream, nail polish) and grooming aids (soap, shampoo, shaving cream, deodorant). Nowadays, cosmetic products are used not only for enhancing appearance but have become an essential care item that may protect, moisturise, repair and nourish skin, hair and nails. Undeniably, cosmetic products come with an element of fantasy and are bought primarily for glamour. Despite of the merging of this industry around the globe, the scientists behind these cosmetic products is yet to make known. When drawing the cosmetics and pharmaceutical industries together, it is known as dermocosmetics where beauty and health meet. In this dermocosmetic area, it is where the chemists and pharmacists play vital roles in cooperating the most advanced research and technology to develop cosmetic products that are effective, safe, and gentle for global customers and for the Earth environment. As products used on the skin, cosmetics require more than mere functional properties. With the knowledge acquired from chemistry, pharmaceutics and pharmacy practice disciplines, it is strongly believed that chemists and pharmacis can contribute and play important roles in dermocosmetics.